Learning Analytics Dashboard Applications. - Verbert, Katrien; Duval, Erik; Klerkx, Joris; Govaerts, Sten; Santos, José Luis (American Behavioral Scientist, 2013)
This article introduces learning analytics dashboards that visualize learning traces for learners and teachers. We present a conceptual framework that helps to analyze learning analytics applications for these kinds of users. We then present our own work in this area and compare with 15 related dashboard applications for learning. Most evaluations evaluate only part of our conceptual framework and do not assess whether dashboards contribute to behavior change or new understanding, probably also because such assessment requires longitudinal studies.